A Mixed Methods Study of a Rapid Rehousing Program for Refugees - Roebuck, Maryann; Aubry, Tim; Buckley, Carol; Dyck, Doreen; Manoni-Millar, Stéphanie; Quds Akbar, Khadija (International Journal on Homelessness, 2026)
Internationally, refugees face financial stress and housing precarity that are worsening due to housing crises and higher levels of displacement. In 2023 to 2024, this study used mixed methods to examine a rapid rehousing program for resettled refugees in Ottawa, Ontario, Canada that supports refugees to access scattered site housing in private market rentals with portable rent subsidies. The study objectives were: 1) To determine program strengths and barriers to program implementation; and 2) To evaluate the outcomes of the program for clients. The researchers used an exploratory-sequential mixed methods design that included analysis of program data, semi-structured qualitative interviews with 10 key informants and 11 program clients, and a client survey (N = 50). The program provides housing stability for refugees using the rapid rehousing model. Out of the 50 clients who completed the survey, 80% were housed in private market rentals. Clients also described positive employment and education outcomes and improved social connectedness.